Analisis Komparatif Efektivitas dan Kapabilitas Implementasi Laboratorium Virtual Internet of Things (IoT) Berbasis Emulasi Mikrokontroler dengan Dukungan MicroPython - San Vitores Jemalut; Muhammad Priyono Tri Sulistyanto; Moh Ahsan (SMARTICS Journal, 2025)
This research analyzes the implementation and effectiveness of virtual laboratories in Internet of Things (IoT) education through microcontroller emulation, specifically with MicroPython support. Physical infrastructure constraints and operational costs have prompted a shift in learning paradigms toward virtual solutions. This paper compares the capabilities of two primary emulator categories—online solutions (Case Study: Wokwi) and offline solutions (Case Study: QEMU/Espressif Fork)—based on accessibility, emulation fidelity, and pedagogical effectiveness. The results indicate that online emulators like Wokwi excel in accessibility and ease of end-to-end integration (Wi-Fi simulation), which has been proven to yield significant improvements in student competency (average N-Gain score of 74.6%) in academic case studies. Functional case study implementation using Wokwi with Thingsboard demonstrates effectiveness in illustrating end-to-end IoT workflows from virtual sensors to the cloud via the MQTT protocol. Conversely, QEMU provides deeper register-level emulation accuracy, establishing it as a vital instrument for advanced firmware development and debugging. A hybrid implementation model and the use of free cloud platforms are recommended for introductory-level education.